Sensory Quality, Volatile Compounds, and Physical Properties of Sheep’s Milk Cheese with Herbs (Allium ursinum L.) - Agnieszka Pluta-Kubica; Dorota Najgebauer-Lejko; Jacek Domagała; Jana Lakatošová; Marek Šnirc; Jozef Golian (Molecules)
The aim of this study was to investigate the effect of the addition of wild garlic leaves on the sensory quality, volatiles, color, and texture of sheep milk soft rennet-curd cheese. The sensory evaluation of color, appearance, texture, odor, and taste was performed using a 5-point scale. The intensity of selected taste and odor discriminants was also assessed. Volatiles were analyzed by the GC-MS method. Color and textural characteristics were determined instrumentally. The wild garlic addition had no effect on the sensory characteristics of the cheese (p > 0.05). However, cheese with herbs exhibited a less intensive sour odor (p ≤ 0.05), sheep’s milk odor, and taste (p ≤ 0.01). (E)-7-methyl-4-decene, dichloroacetic acid undecyl ester, and 3,5-dimethyl-octane, described as creamy, acetic, and acid pungent in smell, were not detected in the cheese with wild garlic while they were present in the natural one. Moreover, herbal cheese was more piquant (p ≤ 0.01). PCA showed that the differences in volatiles resulted both from the use of wild garlic and the time of storage. Herbal addition affected almost all color characteristics, except for the hue angle (h), but caused an increase only in hardness and chewiness. In conclusion, wild garlic leaves can be recommended as an additive in the production of soft sheep’s milk rennet-curd cheese.